Pengaruh Profitabilitas, Ukuran Perusahaan, Financial Leverage, Kepemilikan Institusional, Dan Jenis Industri Terhadap Praktik Perataan Laba(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2012-2014) - Kuswara, Ricky Aditya Angga, Dr. Triyono, S.E., M.Si (2016)
This study aims to test empirically the impact of profitability, firm size, financial leverage, institusional ownership, and type of industry on income smoothing practice. Population of this study is all of manufacturing companies listed in Indonesian Stock Exchange during 2012-2014. This study used purposive sampling method to collect the sample. Based on certain, there were 185 go public companies that match as the samples. The analysis of statistic on this study used multiple regression analysis. The results of this study show that profitability, firm size, financial leverage, and institusional ownership have the significant effect on income smoothing practice but the type of industry have not the significant effect on income smoothing practice.